Bioactive sesterterpenoids from the fungus Penicillium roqueforti YJ-14. (July 2021) - Wang, Jia-Peng; Shu, Yan; Liu, Rui; Gan, Jun-Li; Deng, Si-Ping; Cai, Xue-Yun; Hu, Jun-Tao; Cai, Le; Ding, Zhong-Tao
Abstract: Seven previously undescribed sesterterpenes were characterized from Penicillium roqueforti YJ-14 by solid fermentation. Their structures were initially investigated in detail by spectroscopic analyses and HR-ESI-MS and were further confirmed by X-crystallography. In in vitro bioassays, compounds 1, 5 and 7 showed cytotoxic activity against the MCF-7 breast cancer cell line with IC50 values of 7.98 ± 0.93, 6.42 ± 0.41 and 7.32 ± 0.18  μ M, respectively. Compounds 5 and 7 displayed significant cytotoxicity against the A549 lung cancer cell line (IC50 values of 4.83 ± 0.22  μ M and 4.58 ± 0.85  μ M, respectively). In addition, compound 5 showed an obvious inhibitory effect on nitric oxide production in LPS-activated RAW264.7 macrophages with an IC50 value of 9.53 ± 0.16  μ M. Graphical abstract: Image 1 Highlights: Seven new sesterterpenes were isolated from Penicillium roqueforti YJ-14. Three compounds showed cytotoxic activity. One compound showed anti-inflammatory activity.